PELAKSANAAN MEDIASI DI MAHKAMAH SYAR’IYYAH MEUREUDU - Dedy Muvizar (AHKAMUL USRAH: Jurnal S2 Hukum Keluarga dan Peradilan Islam, 2021)
Divorce under certain circumstances is inevitable. In the face of many requests for divorce, the Judge of the Sar'iyah Meureudu Court required mediation. To minimize the divorce rate or a husband and wife canceling their divorce, but creating a peace agreement between the husband and wife was still good. The purpose of this study was to determine the effectiveness of mediation, the stages of mediation, and the supporting and inhibiting factors for the success of mediation at the Mereudu Syar'iyah Court. This research is field research with a descriptive analysis approach. The data collection technique used is sociological juridical through observation, interviews, and documentation. The results showed that the success of mediation at the Meureudu Syar'iyah Court was caused by several factors. The most dominant factor is the child factor and family support. The inhibiting factor of mediation is the unanimous determination of husband and wife to divorce. The effectiveness of mediation at the Meureudu Syar'iyah Court has been good. The mediation success rate is 34%. The details are 53 cases were entered, two were successful, and 15 were partially successful. This figure looks small when viewed from the percentage figures alone, but in terms of the difficulty of achieving successful mediation, the percentage is quite large.